Achieving sustainable development goals through board size and innovation. (28th October 2021) - Chindasombatcharoen, Pongsapak; Chatjuthamard, Pattanaporn; Jiraporn, Pornsit; Treepongkaruna, Sirimon
Abstract: Sustainable development is one of the prominent goals promoted by the United Nations (UN). To achieve Sustainable Development Goals, the UN identifies innovation as one of the important elements. Motivated by this, we explore how board size affects firm's innovation and find a negative relation between board size and firm's innovation. Our analyses including ordinary least squares (OLS) regressions, instrumental variable, propensity score matching, and generalized method of moment (GMM) dynamic panel data estimation show that our results are robust and are not driven by unobserved heterogeneity. Our findings are consistent with stewardship theory where a smaller board leads to more corporate innovation, which eventually leads to sustainable firms.